Effects of Foot-Core Training on Foot-Ankle Kinematics and Running Kinetics in Runners: Secondary Outcomes From a Randomized Controlled Trial - Matias, Alessandra B.; Watari, Ricky; Taddei, Ulisses T.; Caravaggi, Paolo; Inoue, Rafael S.; Thibes, Raissa B.; Suda, Eneida Y.; Vieira, Marcus F.; Sacco, Isabel C. N. (Frontiers in Bioengineering and Biotechnology, 2022)
This study investigated the effectiveness of an 8-week foot-core exercise training program on foot-ankle kinematics and running kinetics, with particular interest in biomechanical outcomes considered risk factors for running-related injuries in recreational runners. A single-blind, randomized, controlled trial was conducted with 87 recreational runners randomly allocated to either the control (CG) or intervention (IG) group and assessed at baseline and after 8 weeks. The IG underwent foot-core training 3 times/week, while the CG followed a placebo lower-limb stretching protocol. The participants ran on a force-instrumented treadmill at a self-selected speed while foot-segment motion was captured simultaneously with kinetic measurements. After the intervention, the participants in the IG struck the ground with a more inverted calcaneus and a less dorsiflexed midfoot than those in the CG; at midstance, ran with a less plantarflexed and more adducted forefoot and a more abducted hallux; and at push-off, ran with a less dorsiflexed midfoot and a less adducted and more dorsiflexed hallux. The IG runners also had decreased medial longitudinal arch excursion and increased rearfoot inversion. The 8-week foot-core exercise program had no effect on impact and breaking forces or on loading rates, but it was effective in changing foot-ankle kinematic patterns.